The Existence of Madrasahs in Social Mobility - Nurbuana Nurbuana; Abdullah Idi; Karoma; Afryansyah; Agus Wahyudi (The Future of Education Journal, 2024)
Madrasahs, as Islamic educational institutions, hold a crucial position in fostering social mobility within society. This study aims to explore the connection between madrasahs and social mobility through a literature review approach. Madrasahs play a pivotal role in elevating the social status of their students by offering a blend of religious and general education. The findings highlight that madrasahs significantly contribute to shaping individuals who are not only grounded in Islamic values but also equipped with modern competencies, enabling them to make positive contributions to society. By integrating religious teachings with contemporary knowledge, madrasahs prepare students to navigate both the spiritual and worldly aspects of life, positioning them as agents of change. As such, the continued existence and development of madrasahs emphasize their relevance as dynamic educational institutions capable of addressing the diverse social and cultural challenges of the modern world.